Do Local Institutions Matter? A Multilevel Examination Of The Effects Of Neighborhood Churches And Service Providers On Parolee Outcomes - Headley, Rebecca Ann (2017)
Each year 700,000 to 800,000 parolees are released prison and are returned to the community (Durose, Cooper, & Snyder 2014; Porter, 2011; West, Sabol, Greenman, 2010), of whom approximately two-thirds will be reincarcerated within the three years following their releases (Durose et al., 2014). Although, scholars have pointed to parolees’ needs of services and resources (Hipp, Petersilia, & Turner, 2010), the majority of the literature has been limited to the examination of individual-level predictors of parolee outcomes. The current study aims to extend the parolee literature by identifying whether or not neighborhood disadvantage, mobility, and local institutions (i.e., churches, service providers) have an effect on parolee outcomes. To examine these effects, data on 3,077 parolees living within 209 Census block groups across Philadelphia, Pennsylvania were obtained from the Pennsylvania Department of Corrections (PA DOC) and the Pennsylvania Board of Probation and Parole (PBPP). Furthermore, parolee outcome data were disaggregated by the behavior resulting in reincarceration [i.e., the commission of a new crime (CPV), technical parole violation (TPV)], as well as the length of time between release from prison and reincarceration. A series of multilevel models (HLM) were conducted to examine the effects of neighborhood-level and individual-level predictors of parolee reincarceration, as well as how these effects differed for CPVs versus TPVs, and varied across time. Based on results from the analyses, parolee outcomes were to some extent effected by neighborhood context and institutions (i.e., Evangelical Protestant churches, service providers). Additionally, neighborhood-level and individual-level effects varied based on the reason for reincarceration, and the amount of time that passed between release from prison and reincarceration. Lastly, although DOC referred service providers did not have a direct effect on parolee reincarceration, there were significant interaction effects with disadvantage, such that the effects of DOC service providers decreased the odds of reincarceration in more disadvantaged neighborhoods. The conditional effects of DOC service providers by level of neighborhood disadvantage highlights the need for service providers within such communities. Further investigation of neighborhood context, and the placement of much needed resources in communities where parolees reside, may be advantageous in increasing success amongst parolees